Foraging patterns of breeding Dolphin Gulls Larus scoresbii at Punta Tombo, Argentina - Suárez, Nicolás; Yorio, Pablo Martin (Ibis)
The Dolphin Gull Larus scoresbii is a little‐known, rare species endemic to southern South America. Knowledge of its feeding ecology is essential for development of management and conservation strategies. To obtain information on their use of food resources and on the frequency and duration of their foraging trips, we followed seven individuals by radiotelemetry during the breeding season of 2002 at the Punta Tombo Reserve, Argentina. In 99% of mapped locations (n = 4069) the Gulls were within 2.4 km of their colony. Dolphin Gulls foraged mostly at the colonies of three other species, feeding on Magellanic Penguin Spheniscus magellanicus and Imperial Cormorant Phalacrocorax atriceps regurgitates and on Southern Sea Lion Otaria flavescens faeces. The sea lion colony was the most frequently visited foraging area, accounting for 64% of the total (n = 260 trips). A similar trend was observed during both the incubation (60%, n = 38 trips) and the chick (64%, n = 40 trips) stages. The mean number of trips per day was 3.8 (range = 3–5), with a mean duration of 123 min (sd = ±27). Trip duration differed between foraging areas, being significantly longer at the sea lion than at the penguin and cormorant colonies. The small foraging range given by its particular feeding strategy suggests that Dolphin Gulls, in contrast to most other seabirds that range over large expanses of ocean in search of food, may be effectively conserved within protected areas during the breeding season. Fil: Suárez, Nicolás. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Yorio, Pablo Martin. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos